THE ANALYSIS OF ISLAMIC THEOLOGY TOWARD MANDI SAFAR RITUAL IN AKIT TRIBAL BENGKALIS-RIAU - Suroyo, Suroyo; Putra, Bima Maulana; Ratnawati, Sri (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
Mandi Safar (Safar bathing) ritual is a tradition of rejecting reinforcements and a means of gathering for the coastal by Local Malay community in Rupat Island of Riau Province. This is an annual event. The purpose of this research is to show the local Islamic community's bathing Safar rite, which has attracted the attention of many Islamic theology. However, the event creates both benefits and drawbacks among those who support and oppose it. As a result, the goal of this research is to give an overview and analyzing of the influence of Islamic theology toward Mandi Safar ritual. This is a qualitative ethnographic study that highlights the role of researchers as the key instrument in the research process. This research's informants are local communities and their leaders, as well as culture experts, with a total of ten informants residing on Rupat Island. They comprehend the importance of these rites and skills in their everyday lives, as well as the responsibility of local governments in preserving this tradition. Malay culture and the local population of Rupat Island thinks that the month of Safar brings a bala' and ailment, thus they perform the Safar bath ritual, which includes reading chosen letters from the Qur'an, ablution, prayer congratulations, and prayer rejections. Safar bath has its purpose in the month of Safar to get safety and prevent ill luck. The novelty of this research lies in the unveiling the Islamic theology influence toward Safar bathing from the Koran and hadith.